Pengembangan Buku Ajar Matematika Berbasis Flipbook Menggunakan Model Collaborative Problem Solving pada Materi Bangun Ruang - Kusumayanti, Andi; Rusmiati, Ayu (Alauddin Journal of Mathematics Education, 2022)
This study discusses the development of flipbook-based mathematics textbooks using the Collaborative Problem Solving (CPS) learning model. This research was conducted with the aim of knowing the process of making flipbook-based mathematics textbooks using a valid, practical, and effective Collaborative Problem Solving (CPS) learning model. The type of research used is Research & Development (R&D) research with reference to the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The test subjects in this study were 6 students of class VIII SMP Muhammadiyah Belawa, Wajo Regency. The product assessment techniques and instruments used consisted of textbook validation sheets, student and teacher response questionnaires, student and teacher activity observation sheets, and student mathematics learning outcomes tests. Based on the results of data analysis, it was obtained that the akat book (1) was valid, the validation results from the validator on the content aspect obtained an average score of 3.00 with a valid category, the average score of the language aspect was 2.75 with a valid category, the average score of the presentation aspect 3.06 in the valid category, the average score for the graphic aspect is 2.93 in the valid category, and the average score for all aspects of textbook assessment is 2.94 in the valid category, and (2) Practical, the average score on the display aspect is 3.50 in the positive category, the content presentation aspect is 3.63 in the positive category, the benefit aspect is 3.67 in the positive category, and the average score for all aspects is 3.60 in the positive category. So, it was concluded that the flipbook-based mathematics textbook using the Collaborative Problem Solving (CPS) learning model for class VIII students of SMP Muhammadiyah Belawa, Wajo Regency, was developed to be valid and practical.